Associations between neutrophils and amyloid deposition in the Alzheimer's disease spectrum. (31st December 2021) - Rahmouni, Nesrine; Tissot, Cécile; Lussier, Firoza Z; Bezgin, Gleb; Therriault, Joseph; Stevenson, Jenna; Stevenson, Alyssa; Chamoun, Mira; Kang, Min Su; Pascoal, Tharick A.; Gauthier, Serge; Benedet, Andréa Lessa; et al.
Abstract: Background: Neutrophils are key components of early innate immunity and contribute to uncontrolled systemic inflammation. Several studies have highlighted the link between systemic inflammation and the Alzheimer's disease (AD) pathophysiology. In fact, experiments with animal models and studies with AD patients demonstrated the hyperactivation of neutrophils associated with AD pathology and cognitive decline. However, the comprehension of the inflammatory component in the AD spectrum is still uncomplete. We thus investigated whether the amount of systemic neutrophils is correlated with brain amyloid‐β in the AD spectrum Method: The present study was conducted in a population of 170 individuals (115 cognitively unimpaired (CU) and 55 cognitively impaired (CI; 35 MCI and 20 AD) from the Translational Biomarkers in Aging and Dementia TRIAD cohort. The neutrophil relative values were assessed using the Automated Beckman DXH hematology Analyzer. Amyloid (Aβ) deposition was assessed with [ 18 F]AZD4694 PET. A voxel‐based regression model evaluated the relationship between neutrophil count and Aβ PET, adjusted for age, sex, years of education and diagnosis. RFT was used to account for multiple comparisons. Result: In the present study, a positive association was found between systemic neutrophil counts and brain Aβ load, where the associated regions were the anterior cingulate, cuneus, and occipital pole areas. Also, CI individuals showed significantly higher neutrophil counts as compared to the CU group. Conclusion: Our findings review the link between the peripheral immune system and the central nervous system amyloid deposition. Further studies should investigate the use of neutrophil counts as biomarkers of AD.